Impact of cataract surgery in quality of life of patients - Gupta, Surbhi; Gupta, Riya; Gupta, Rajiv K (International Journal of Research in Medical Sciences, 2021)
Background: Loss of vision invariably leads to loss of quality of life (QOL), which represents the general well-being of individuals and societies. Researchers have tended to indicate that visual acuity (VA) alone is an inadequate measure of visual impairment. Studies on QOL after cataract surgery are scarce in this part of India and there our present study holds potential to be really useful. Methods: This study was a prospective study consisting of 300 patients aged 50 years and above, who were operated for cataract in the Department of ophthalmology, GMC Jammu from May 2017-February 2018, a period of 10 months. Visual acuity was measured by logMaR method and generic health related quality of life (HRQoL) was measured using EuroQol (EQ-5D). Results: Only 182 turned up for the follow up after six months, mainly belonging to the age group: 60 to 70. 66.48% of the people studied upon belong to the lower strata of the society. Substantial improvement in visual acuity was observed with only 3.84% of patients showing less than 6/60 visual acuity during follow up after 6 months. All domains related to the generic health related QOL showed improvement. There was clear and marked improvement for performance of usual activities by the patients after surgery. Conclusions: In conclusion this study has provided valuable information about the change in vision related quality of life after cataract surgery there is statistically significant improvement in QOL of all patients enrolled in our study after the cataract surgery.